Complement Activation in Mycoplasma fermentans-Induced Mycoplasma Clearance from Infected Cells: Probing of the Organism with Monoclonal Antibodies against M161Ag - Kikkawa, Satomi (American Society for Microbiology, 2000)
Mycoplasma fermentans, a cell wall-less prokaryote, is capable of infecting humans and has been suggested to serve as a cofactor in AIDS development. Recently, we discovered a novel lipoprotein with a molecular mass of 43 kDa originating from M. fermentans. This protein, named M161Ag, activated human complement via the alternative pathway and efficiently induced the proinflammatory cytokines interleukin 1β (IL-1β), tumor necrosis factor alpha, IL-6, IL-10, and IL-12 in human peripheral blood monocytes. It is likely that M161Ag of M. fermentans affects the host immune system upon mycoplasma infection. In this study, we developed monoclonal antibodies (MAbs) against M161Ag and examined the direct role of complement in M. fermentans infection using these MAbs as probes. M. fermentans was rapidly cleared from the surfaces of infected cells by human complement, but a low-grade infection persisted in human tumor cell lines. Mycoplasma particles remaining alive in host cells may cause recurrent infection, and liberated M161Ag may serve as a biological response modifier affecting both innate and acquired immunity.